Manajemen dan Kepemimpinan Pendidikan Islam di Era Globalisasi - Tobroni, Tobroni (Nadwa, 2012)
Many researches appoint that to change from negative cycle become positive cycle or change from bad quality school become good quality school, leadership factor is an important and defined role. The good education institution is leaded by good leader, although not all of good leader can make it become good educa-tion institution. For Islamic education institution which faces difficult affairs and has a great mission (education and missionary work), needs to be led by a leader who has powerful strength. Conventional leadership models like situational, transactional, and transformational leadership need to be completed with spir-itual leadership. Spiritual leadership is a leadership which bases its leadership vision, mission and attitude on theology values.